PENGARUH JENIS BAHAN PEREKAT DAN METODE PENGERINGAN TERHADAP KUALITAS BRIKET LIMBAH BAGLOG JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Siti Mushlihah; Sulfahri; Renia Setyo Utami; Eko Sunarto; I.D.A.A. Warmadewanthi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
White mushroom is one of popular food commodity in East Java. Every year total production of white mushroom is more than 4800 ton. The cultivation of this mushroom needed the medium known as "baglog". Every 3 month the medium should be changed. The huge amount of solid waste will be produced around 40 tons/month and must be managed by farmer. Based on the composition of waste contains 80% of sawdust and 10% of rice brain. This composition known has a high concentration of carbon and potential as a material to produce of energy. This research investigated the effectiveness of "baglog" from medium of white mushroom cultivation as a briquette for energy alternative. Different variables used in this experiment are drying process and material that used as an adhesive for making of the briquette. The quality of the briquette such as energy value, compressive strength of briquette, moisture, fixed carbon and emission of briquette, was analyzed, based on Indonesia Standard. Result of the experiment showed that energy value of the briquette is 3400 cal/gram with drying process using oven. The compressive strength result showed that the adhesive using starch glue is very effective. This briquette is environmentally friendly